Sistem Pendukung Keputusan dalam Merekomendasikan Unit Terbaik di PDAM Tirta Lihou Menggunakan Metode Promethee - Tia Imandasari; Agus Perdana Windarto (Department of Computer Engineering, Engineering Faculty, Universitas Diponegoro, 2017)
This research aims to develop decision support system in determining the best production unit in PDAM Tirta Lihou, Simalungun District. The research data were sourced from the institution in 2014. The alternatives used were 34 units of production and 6 criteria as the ranking of the best production unit such as the criteria for selling of water supply (C1), evaluation of arrears achieved (C2), evaluation of leakage rate (C3), running bill evaluation (C4), number of new customers (C5) and sales / use of water per customer (C6). The method used in this research was Promethee. The research showed that the best unit in PDAM Tirta Lihou was the Tanah Jawa unit with Net Flow 0.16274. With this system, agency leaders can produce a better decision to select the best unit in a more objective way.(The data set and data results in this study are available in the supplementary section available online and downloadable)